Conclusion: What We Found and What We Recommend - Kibaroğlu, Ayşegül; Schmandt, Jurgen; Ward, George H. (Cambridge University Press, 2021)
This interdisciplinary volume examines how nine arid or semi-arid river basins with thriving irrigated agriculture are doing now and how they may change between now and mid-century. The rivers studied are the Colorado, Euphrates-Tigris, Jucar, Limarí, Murray-Darling, Nile, Rio Grande, São Francisco, and Yellow. Engineered dams and distribution networks brought large benefits to farmers and cities, but now the water systems face multiple challenges, above all climate change, reservoir siltation, and decreased water flows. Unchecked, they will see reduced food production and endanger the economic livelihood of basin populations.

The multi-year research effort in this volume has demonstrated that (1) similar challenges are faced by all SERIDAS rivers, (2) problem recognition varies widely across basins, and (3) response strategies are not sufficiently grounded in the long-term goal of river sustainability. We recommend that river managers and stakeholders follow these guidelines: Determine the river’s dependable yield – the water supply, averaged over the period of the most severe drought experienced in the historical record. Use the dependable yield to define and implement a river management strategy that carefully balances human and ecological needs in the basin. To meet human needs, do more with less – practice water conservation. This is the best obtainable strategy for redefining and maintaining river sustainability. © Jurgen Schmandt, Aysegul Kibaroglu, Regina M. Buono and Sephra Thomas 2021.
Keywords: Challenge and Response; Dependable Yield; River Basin Management; River Sustainability; Sustainability Recommendations; Water-Supply – Management; Watershed Management; Water Resources Development